Enhancement of Hot Mix Asphalt stability by utilizing Cement Kiln Dust and Styrene-Butadiene-Styrene Polymer - F. Abbas, Hiader; H. Abed, Alaa (Al-Nahrain Journal for Engineering Sciences, 2023)
Utilization of additives can be an effective way to improve the durability and performance of HMA, making them more resistant to Moisture and deformation. Plus, they can reduce the need for maintenance and repairs, saving you time and money in the long run. In this study,  CKD was used in place of limestone as a filler in the asphalt mixture in proportions of 0%, 25%, 50%, 75%, and 100%, and polymer SBS 4%by weight of asphalt. According to the findings, replacement-content CKD had the highest asphalt content. When the CKD is between 25% and 50%, Stability, Flow, and Indirect Tensile Strength are improved, while the density of the asphalt mixture decreases and the amount of air voids increases at higher ratios. While SBS leads to an increase in the hardness of the adhesives. As a consequence, the stability of the SBS-containing mixes resulted in higher values than the control and additive-containing mixtures (CKD), as well as a decrease in the number of air voids. According to the results, CKD should not constitute more than half of the filler weight in the asphalt mixture.